2012
DOI: 10.4236/abb.2012.37105
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric biomaterial hydrogels. I. Behavior of some ionotropic cross-linked metal-alginate hydrogels especially copper-alginate membranes in some organic solvents and buffer solutions

Abstract: The change in rheological and mechanical properties for some ionotropic cross-linked metal-alginate hydrogel complexes in particularly copper-alginate membranes in the presence of some organic solvents (benzene, toluene, xylene, carbon tetrachloride, ace-tone, chloroform, dichloroethane, isobutyl alcohol and ethyl alcohol) or buffer solutions (acetates, borates and universal buffers) have been investigated. The experimental results showed a remarkable tendency of the studied hydrogels for shrinking in polar so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This is in agreement with the research work in Hassan et al . 41 which focused on the ionotropic cross-linking of metal alginate. They showed that the cross-linking of alginates with divalent metal ions at a stoichiometric ratio of 2:1 which correlates with this result of the pseudo-second-order kinetics fitting.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the research work in Hassan et al . 41 which focused on the ionotropic cross-linking of metal alginate. They showed that the cross-linking of alginates with divalent metal ions at a stoichiometric ratio of 2:1 which correlates with this result of the pseudo-second-order kinetics fitting.…”
Section: Resultsmentioning
confidence: 99%
“…However, rich carboxylic acid (-COOH) and hydroxyl (-OH) groups on this polymer limit cell adhesion (19,20). Chitosan grafting is a common way to enhance hydrophobicity (19,20). In this study, the existence of nanoparticles clearly decreased the contact angle from 97 ± 3°in alginate hydrogel to 61 ± 4°in alginate/chitosan nanoparticle hydrogel.…”
Section: Contact Angle Measurementmentioning
confidence: 68%
“…Among natural polymers, alginate has been extensively used in biomedical application because of its superior degradation ability and nontoxicity of its product. However, rich carboxylic acid (-COOH) and hydroxyl (-OH) groups on this polymer limit cell adhesion (19,20). Chitosan grafting is a common way to enhance hydrophobicity (19,20).…”
Section: Contact Angle Measurementmentioning
confidence: 99%
See 2 more Smart Citations